2017
DOI: 10.1111/mice.12337
|View full text |Cite
|
Sign up to set email alerts
|

Earth Dam Construction Simulation Considering Stochastic Rainfall Impact

Abstract: Effective construction scheme planning is critical for schedule management, but heavy rain can affect construction processes. In previous studies, stochastic rainfall characteristics are often ignored, and their impact on macro‐ and microconstruction states are not depicted comprehensively. This research presents a construction simulation model to design reasonable construction schemes considering impact of stochastic rainfall. First, a rainfall model suitable for areas with heavy rainfall and uneven seasonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Therefore, for the three HRs of the TAHR, the mixed exponential is the most adequate distribution for the estimation of the daily rainfall probabilities. Abas et al (2014), Li et al (2013), Moreno‐Pérez, Woolhiser and Roldán‐Cañas (2014), Wan et al (2005), and Zhang, Znong, Wu, Fei, and Cui (2018) also indicated the use of the mixed exponential for rainfall modeling.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, for the three HRs of the TAHR, the mixed exponential is the most adequate distribution for the estimation of the daily rainfall probabilities. Abas et al (2014), Li et al (2013), Moreno‐Pérez, Woolhiser and Roldán‐Cañas (2014), Wan et al (2005), and Zhang, Znong, Wu, Fei, and Cui (2018) also indicated the use of the mixed exponential for rainfall modeling.…”
Section: Resultsmentioning
confidence: 98%
“…The ability of discrete-event simulation (DES) to incorporate the variability associated with external factors, such as weather, to determine the impact of uncertainty on system outcomes is wellestablished. As presented in Section 2.2 (Table 1), several studies have successfully applied DES to investigate the effects of adverse weather on construction activities [3,15,23,25,29,41], and DES was shown to be a reasonable tool for scheduling construction activities of onshore wind projects [45]. However, a simulation model capable of considering the impact of weather on the activities on onshore wind farm construction has not been developed.…”
Section: Simulation As a Proposed Approachmentioning
confidence: 99%
“…Therefore, the optimal use of resources is a critical task for contractors. Optimizing earthmoving operations has involved the development of various models employing different techniques, including simulation optimization [6,8,9], simulation and genetic algorithm (Parente and Gomez) in [10], computer simulation [11,12], linear programming [13], and artificial intelligence [14].…”
Section: Modeling and Simulationmentioning
confidence: 99%